Assessment of the accuracy of 11 different diagnostic tests for the detection of Schistosomiasis mansoni in individuals from a Brazilian area of low endemicity using latent class analysis - Mesquita, Silvia Gonçalves; Caldeira, Roberta Lima; Favre, Tereza Cristina; Massara, Cristiano Lara; Beck, Lílian Christina Nóbrega Holsbach; Simões, Taynãna César; de Carvalho, Gardênia Braz Figueiredo; dos Santos Neves, Flória Gabriela; de Oliveira, Gabriela; de Souza Barbosa Lacerda, Larisse; de Almeida, Matheus Alves; dos Santos Carvalho, Omar; et al. (Frontiers in Microbiology, 2022)
Background: Schistosomiasis is a parasitic disease associated with poverty. It is estimated that 7.1 million people are infected with Schistosoma mansoni in Latin America, with 95% of them living in Brazil. Accurate diagnosis and timely treatment are important measures to control and eliminate schistosomiasis, but diagnostic improvements are needed to detect infections, especially in areas of low endemicity. Methodology: This research aimed to evaluate the performance of 11 diagnostic tests using latent class analysis (LCA). A cross-sectional survey was undertaken in a low endemicity area of the municipality of Malacacheta, Minas Gerais, Brazil. Faeces, urine, and blood samples were collected from 400 residents older than six years of age, who had not been treated with praziquantel in the 12 months previous to the collection of their samples. The collected samples were examined using parasitological (Helm Test® kit Kato-Katz), molecular (PCR, qPCR and LAMP on urine; PCR-ELISA, qPCR and LAMP on stool), and immunological (POC-CCA, the commercial anti-Schistosoma mansoni IgG ELISA kit from Euroimmun, and two in-house ELISA assays using either the recombinant antigen PPE or the synthetic peptide Smp150390.1) tests. Results: The positivity rate of the 11 tests evaluated ranged from 5.5% (Kato-Katz test) to 40.8% (commercial ELISA kit). The estimated prevalence of schistosomiasis was 10% (95% CI: 7-13%) according to the LCA. Among all tests assessed, the commercial ELISA kit had the highest estimated sensitivity (100%), while the Kato-Katz had the highest estimated specificity (98%). Based on the accuracy measures observed, we proposed three two-step diagnostic approaches for the active search of infected people in endemic settings. The approaches proposed consist of combinations of commercial ELISA kit and molecular tests performed on stool. All the approaches had higher sensitivity and specificity than the mean values observed for the 11 tests (70.9% and 88.1%, respectively). Conclusion: We showed that it is possible to achieve high specificity and sensitivity rates with lower costs by combining serological and molecular tests, which would assist in the decision-making process for appropriate allocation of public funding aiming to achieve the WHO target of eliminating schistosomiasis as a public health problem by 2030.